Peat filter performance under changing environmental conditions - Kalmykova, Y.; Strömvall, A.; Rauch, S.; Morrison, Greg (Elsevier BV, 2009)
Peat is a candidate filter material for in situ treatment of urban runoff, contaminated groundwater and landfill leachates. Until now research has focused on peat sorption in batch experiments and there is a lack of knowledge on peat performance in filter beds. In this project column tests were carried out to evaluate the capacity of peat to remove As, Cd, Cu, Cr, Ni, Pb and Zn in multi-metal solution under a range of environmental conditions that may be encountered in real-life applications (draining, water stagnation, freezing, change in pH and metal concentrations, input of NaCl and elevated DOC). The removal capacity was 91-98% for Cd, Cu, Zn, Ni and Pb and the efficiency was unaffected by the changes of physical factors, but temporarily inhibited for solutions containing NaCl. Leaching of DOC from peat was detected in the initial samples and temporarily decreased metal removal. The peat filters showed high removal rates for Cd, Cu, Zn, Ni and Pb under all experimental conditions and are recommended for treatment of waters containing these elements. In contrast, peat was not found to be efficient for treatment of As and Cr in the multi-metal contaminated water at the pH range (6.7-8.0) studied. © 2008 Elsevier B.V. All rights reserved.